KOMUNIKASI KELOMPOK IKATAN MAHASISWA MINANG UNIVERSITAS RIAU (IMAMI UR) DALAM MEMBANGUN SOLIDARITAS ANGGOTA - Yosi Eka Nofrima; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
IMAMI UR is one of the Association minang active student at the University of Riau. Imami UR in running the organization formed a group communication. communications groups in the IMAMI UR formed with the goal of one of them is to build solidarity members. For that reason, this study aims to determine the IMAMI UR group communication views of the role of communicators group, the messages that are exchanged, patterns of interaction and communication networks as well as members solidarity.This study uses qualitative methods. As for the subject of the Informants were selected using a purposive technique. Informan of this reasearch consisted of three board consisting of a chairman, secretary and public relations and the two members of the IMAMI UR. Data collection techniques used observation, interview, and documentation.The results of this research show that members of IMAMI UR have roles according to the group structure. As a well-structured group, messages delivered in the interaction is about the performance of the group members. Interaction patterns that formed on IMAMI UR progresses through inter-personal communication. Communication network that also formed, from this interactuin is all channels network communication. IMAMI UR members uphold the norms of decency. And solidarity group formed is organic and mechanical solidarityKeywords : Communication, Group Communication, Solidarity